Spider Web DNA Metabarcoding Provides Improved Insight into the Prey Capture Ability of the Web-Building Spider Tetragnatha keyserlingi Simon (Araneae: Tetragnathidae) - Jie Sun; Xuhao Song; Bin Wang; Dongmei Chen; Tingbang Yang; Shichang Zhang (Agriculture, 2025)
Spiders play a crucial role as predators in terrestrial ecosystems, particularly in controlling insect populations. Tetragnatha keyserlingi Simon (Araneae: Tetragnathidae) is a dominant species in rice field ecosystems, where it builds webs amidst rice clusters to capture prey. Despite its known predation on major rice pests like rice planthoppers, comprehensive field reports on its prey composition are scarce. Herein, we performed a field investigation to explore the population dynamic relationships between T. keyserlingi and major rice pests. Additionally, we employed DNA metabarcoding to analyze the prey spectrum of this spider from both the spider’s opisthosoma and its web. The results showed that the population dynamics of T. keyserlingi and Nilaparvata lugens (Stål) displayed synchrony. Dietary DNA metabarcoding analysis revealed that, compared with the opisthosoma, DNA extracted from spider webs exhibited a higher abundance of prey reads and yielded a higher diversity of identified prey species. Phytophagous pests were the dominant prey group identified in both sample types. In web samples, the most abundant prey reads were from Chironomidae, followed by Delphacidae, Ceratopogonidae, Aleyrodidae, Muscidae, Coenagrionidae, and other prey families. Notably, Delphacidae constituted the predominant prey reads identified from the spider’s opisthosoma, and the corresponding positive rate for Delphacidae was 86.7%. These results indicate that the web of T. keyserlingi can capture a diverse range of prey in rice fields. Among the prey captured by the spider web, rice planthoppers appear to be a primary dietary component of T. keyserlingi, emphasizing its potential as a biocontrol agent for rice planthoppers in integrated pest management strategies. Leveraging spider web DNA metabarcoding enhances our understanding of T. keyserlingi’s prey capture ability, as the residual prey DNA in webs provides critical insights into the foraging dynamics and ecological interactions of web-building spiders.